English Vowel Perception in Spanish-English Bilingual Preschoolers: Multiple-Talker Input Is Only Beneficial for Children With High Language Exposure Levels. - Montanari, Simona; Steffman, Jeremy; Mayr, Robert (Journal of Speech, Language & Hearing Research, 2024)
Purposes: This study examines English vowel perception in Spanish-English bilingual preschoolers, comparing bilinguals' perception patterns to those of monolinguals and examining how child internal (age) and external variables (input quantity and input diversity) predict perceptual performance. Method: Sixty children between 3;6 and 5;6 (years;months) of age participated in the study, 28 of whom were Spanish-English bilinguals and 32 English monolinguals. Perception was assessed through a forced-choice minimal-pair identification task in which children heard synthesized audio stimuli (i.e., "sheep" and "ship") that varied systematically along the / continuum and were asked to match them with one of two pictures. The data were analyzed with Bayesian mixed-effects logistic regression analyses, modeling responses as a function of continuum step, language background (monolingual or bilingual), age, English exposure (i.e., input quantity), and number of English input providers (i.e., input diversity). Results: The results indicate that, despite displaying nonnative English stop voicing perception in a previous study, the same bilingual children showed English /i-1/ perception patterns that did not differ from those of monolinguals. While age did not predict vowel perception, input quantity and diversity jointly interacted to moderate how well children perceived the /i-1/ contrast. Specifically, diverse input promoted perceptual performance in children who received high levels of English exposure--and who presumably had more advanced English language skills, whereas it limited perceptual performance in children with more limited English exposure and skills. Conclusions: This study shows that bilingual children can show monolinguallike perception patterns for some sounds while displaying nontarget perception for others. This is the first study to demonstrate that language exposure mediates the role of input diversity on speech sound development, suggesting that varied input can be more or less beneficial for speech sound development based on the learner's language learning stage.